132k views
5 votes
Choose the correct simplification of (2xy2)2(y2)3.

A. 2x2y10
B. 4x2y9
C. 4x2y10
D. 2x2y9

User Pawel Maga
by
6.0k points

2 Answers

2 votes

Answer:

C.4x^2y^10

Explanation:

Given: (2xy^2)^2 .(y^2)^3

Use the exponent power of power rule : (a^n)^m = a^(mn)

(2xy^2)^2 .(y^2)^3 = (2^2. x^2.y^4).y^6

= 4x^2.y^4.y^6

Use the exponent base rule: a^m. a^n = a^(m + n)]

= 4.x^2.y^(4 + 6)

= 4x^2.y^10

Answer is C.4x^2y^10

Hope this helpful.

Thank you.

User Hugo Alves
by
6.8k points
0 votes
The correct simplification would be 4x2y10. For this problem we should remember that we can only combine like terms and also it is important to know rules of exponents. We do as follows:

(2xy2)^2(y2)^3
2²x²y⁴ (y⁶)
4x²y¹⁰
User Billy Coover
by
6.3k points